Pengaruh Likuiditas, Solvabilitas, dan Aktivitas Terhadap Harga Saham Perusahaan Sektor Healthcare yang Terdaftar di Bursa Efek Indonesia - Sarah Nurlita Sari; Fatimah Fatimah; Choiriyah Choiriyah (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2022)
This study aims to determine the effect of liquidity, solvency, and activity on stock prices in healthcare sector companies listed on the Indonesia Stock Exchange. Sampling using non-probability sampling with purposive sampling method, the sample used is 13 companies. The data required is secondary data obtained from the Indonesia Stock Exchange through the website www.idx.co.id and the data collection method is using the documentation method. The analysis technique used in this research is multiple linear analysis technique, classical assumption test and hypothesis testing. The results of the multiple linear regression Y = 47.647 + 243.648X1 + 232.689X2 + 582.943X3), F test (simultaneous test) with Significant of F 0.000 < 0.05, meaning that there is an influence between Liquidity, Solvency, and Activity together on stock prices and t test (Partial Test) on Significant Liquidity 0.000 < 0.05. Thus it can be concluded that Liquidity has a significant influence on prices stocks, the Significant Solvency is 0.034 <0.05. Thus it can be concluded that Solvency has a significant effect on stock prices, Significant Activity is 0.000 < 0.05 thus it can be concluded that activity has  a significant effect on stock prices